India - Enskat, Mike; Mitra, Subrata Kumar; Singh, Vijay B. (Elections in Asia and the Pacific ; Vol. 1: The Middle East, Central Asia and South Asia, 2001)
Includes all relevant information on national elections held in India since its independence in 1947. Part I gives a comprehensive overview of India's political history, outlines the evolution of electoral provisions, and presents the current electoral legislation in a standardized manner (suffrage, elected institutions, nomination of candidates, electoral system, organizational context of elections). Part II includes exhaustive electoral statistics in systematic tables (numbers of registered voters, votes cast, the votes for candidates and/or parties in parliamentary elections, the electoral participation of political parties, the distribution of parliamentary seats, etc.).
Published to Oxford Scholarship Online: November 2003
Gesehen am 23.06.2021
Seitenzahlen des Inhaltsverzeichnis der Druck-Ausgabe übernommen
Die pdf-Datei des Aufsatzes hat 41 Seiten